Tilthmaker for once-over soil tillage - M. A. Mosyakov; V. N. Zvolinskiy (Сельскохозяйственные машины и технологии, 2015)
One of modern methods of soil cultivation at reclamation of neglected field is layer-by-layer loosening of the top horizon by various working tools. Combined units have no removable tools. They are used not effectively both for primary cultivation and secondary tillage, and for reclamation of neglected field. This situation limits a scope of machines and reduces their annual loading. A combined unit for operations overlapping at presowing tillage have two-disk sections of frontal harrows, replaceable loosening working tools of subsurface plow and chisel type and replaceable tubular and toothed rollers. The authors developed agrotechnical requirements of design data of replaceable suspensions of disk sections, duckfoot sweeps and rollers. A placement of working tools on a universal frame provides an opportunity to have15 options of the unit for various agrotechnical and soil climatic conditions. A level of innovative development soil-cultivating the disk and duckfoot units is high, tools rather reliable and universal. Such machines operate different options of the primary and secondary soil cultivation for one pass, replace 4 one-operational machines. The mulch tillage by disk and duckfoot units replaces 2-4 passes of machine-tractor aggregates, saves 2-5 kg/ha of diesel fuel and 0.3 man-hours /ha of labor costs, productivity of winter and spring grain crops increases by 0.3 t/ha.